2022
DOI: 10.1108/ijchm-08-2021-1005
|View full text |Cite
|
Sign up to set email alerts
|

Post COVID-19 recovery for independent full-service restaurants using the salience theory: what will it take to get customers to return?

Abstract: Purpose This study aims to compare customers’ perceived importance of various post-COVID-19 recovery strategies (i.e. sanitary practices, discounts, menu modification and marketing strategies) adopted by independent full-service restaurants (casual dining versus upscale/fine dining) using the salience theory. It also assesses the associations between customers’ perceptions and their restaurant spending patterns. Design/methodology/approach An online survey was administered to assess 657 US adult participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Filipino diners in Dubai have been forced to rely more on alternative dining options such as food delivery services and takeaways. According to a study conducted by Wang et al, diners' patronage intentions were greatly affected by safety measures and the crowdedness of restaurants (Sun et al, 2022). This suggests that the perception of safety plays a crucial role in Filipino diners' decision to eat out or opt for food delivery services during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Filipino diners in Dubai have been forced to rely more on alternative dining options such as food delivery services and takeaways. According to a study conducted by Wang et al, diners' patronage intentions were greatly affected by safety measures and the crowdedness of restaurants (Sun et al, 2022). This suggests that the perception of safety plays a crucial role in Filipino diners' decision to eat out or opt for food delivery services during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Even after the reopening of indoor dining, safety concerns held customers back from dining in restaurants (National Restaurant Association, 2020). COVID-19-related hospitality studies published between 2020 and 2022 identified facilitators and barriers to customers’ dining in restaurants (Kostromitina et al , 2021; Ma et al , 2022; Sun et al , 2022; Tuzovic et al , 2021; Wei et al , 2021). Among several factors, reducing restaurant customers’ anxiety through PM was considered crucial in drawing customers back to in-restaurant dining (Byrd et al , 2022; Jeong et al , 2022; Kim et al , 2021a).…”
Section: Literature Reviewmentioning
confidence: 99%